Thresholds of perception of irregular signal frequency changes - OZIMEK, Edward; SĘK, Aleksander (Archives of Acoustics, 1985)
In the literature, the problem of the perception of signal frequency changes has been considered mainly with reference to regular changes, obtained in the process of frequency modulation of a tone by a tone. There are, however, no publications on the thresholds of the perception of irregular frequency changes. This fact was an encouragement to undertake investigations with the essential purpose of determining the thresholds of the perception of irregular frequency changes for a signal with constant amplitude and a decaying signal with an exponential envelope, depending on: the carrier frequency of the signal, its intensity level and the duration of the decaying signal. The courses of the perception thresholds of irregular frequency changes obtained here are much more general than the data published previously on the subject in the literature. The investigation results obtained permit better knowledge of the mechanism of the so-called dynamic perception of signals, i.e. the perception of signals with parameters varying in time, whose natural counterpart in practice are the sounds of speech and music.